Exceptional Mirizzi syndrome in a young child: A laparoscopic approach - Marcos Prada-Arias; José Luis Vázquez-Castelo; Patricia Blanco-Lobato; Javier Gómez-Veiras; Margarita Montero-Sánchez; Juan Manuel Vieito-Fuentes (Elsevier, 2014)
Mirizzi syndrome is defined as an obstruction of the hepatic duct by an impacted biliary stone in the Hartmann's pouch of the gallbladder or in the cystic duct (Mirizzi type I). The gallstone may erode the bile duct causing a cholecystobiliary fistula (Mirizzi type II). This very rare complication of long standing cholelithiasis is mainly reported in adults. We report an exceptional case of a type I Mirizzi syndrome in a 3-year-old boy, incidentally discovered during a computed tomography study. Ultrasonography and cholangioresonance confirmed the diagnosis. At laparoscopy, partial fusion between the Hartmann's pouch and the hepatic duct was found. Despite difficult dissection, a total laparoscopic cholecystectomy was performed. Preoperative diagnosis of this syndrome is difficult owing to unspecific clinical presentation and low sensitivity of the standard radiological studies. To detect and correctly identify the type of Mirizzi syndrome during surgery is very important in order to avoid serious complications and to perform the most adequate surgical treatment. Open subtotal cholecystectomy is the recommended procedure in Mirizzi type I, laparoscopic total cholecystectomy being possible in some cases. Although this entity is exceptional in children, it must be known and considered by the Pediatric Surgeon because its development is possible.